Are sociodemographic and anthropometric variables effective in screening probable and confirmed sarcopenia in community-dwelling older adults? A cross-sectional study - Souza, Larissa Franciny de; Fontanela, Laís Coan; Leopoldino, Amanda Aparecida Oliveira; Mendonça, Vanessa Amaral; Danielewicz, Ana Lúcia; Lacerda, Ana Cristina Rodrigues; Avelar, Núbia Carelli Pereira de (São Paulo Medical Journal, 2023)
BACKGROUND: Screening for probable and confirmed sarcopenia using sociodemographic and anthropometric indicators can be a practical, cheap, and effective strategy to identify and treat older people susceptible to this condition. OBJECTIVES: To identify cutoff points for sociodemographic and anthropometric variables in screening probable and confirmed sarcopenia in community-dwelling older adults. DESIGN AND SETTING: This was a cross-sectional study of community-dwelling older adults in Araranguá, Santa Catarina, Brazil. METHODS: Sociodemographic (age, education) and anthropometric (weight, height, body mass index [BMI], waist circumference [WC], and dominant calf circumference [DCC]) factors were considered as predictors. The outcomes were probable sarcopenia (reduction in muscle strength assessed by time ≥ 15 s in the five-time sit-to-stand test) and confirmed sarcopenia (reduction in strength and muscle mass). Receiver operating characteristic curve analysis was used to analyze the ability to track sociodemographic and anthropometric variables for sarcopenia. RESULTS: In 308 older adults, WC > 91 cm in women and age > 69 years in men were useful in screening for probable sarcopenia. The variables age, weight, BMI, WC, and DCC can be used to screen for sarcopenia in older women and men. CONCLUSION: Sociodemographic and anthropometric variables are simple and accessible tools for sarcopenia screening in older adults.